Investigation on the mechanical properties of ramie/kenaf fibers under various parameters using GRA and TOPSIS methods - Ganesh, Saikrishnan; Keerthiveettil Ramakrishnan, Sumesh; Palani, Vijayanand; Sundaram, Madhu; Sankaranarayanan, Nagarajan; Ganesan, Suganya Priyadharshini (Polymer composites, 2022)
This work aims to optimize the mechanical performance of ramie and kenaf fibers in epoxy composites developed using the hand layup technique. Fiber reinforcement at 0–10 wt% and benzoyl chloride treatment at 0–5 wt% were incorporated with this composites. Taguchi‐based grey relational analysis (GRA) and technique for order preference by similarity to ideal solution (TOPSIS) methods were used to determine the optimized conditions for overall mechanical properties of the developed composites. Optimization techniques concluded that 10 wt% ramie (R)/10 wt% kenaf (K) with 5 wt% benzoyl chloride treatment (T) based epoxy composites observed good mechanical properties with ultimate tensile strength of 37.39 MPa, ultimate flexural strength of 63.53 MPa, and impact strength of 70.36 J/m due to hybridization and the reduction in hydrophilic nature by the surface treatment process. The optimized GRA and TOPSIS combination with 10 wt% R/10 wt% K/5 wt% of T observed reduced water absorption nature with a contact angle of 64.72°.